S59 Reduction in fatalities following introduction of an initial home oxygen risk mitigation form (IHORM) for all new patients on home oxygen in england and wales. (12th November 2019) - Turner-Wilson, J; Smith, S; Channon, S
Abstract : Introduction: Home Oxygen can be ordered by any registered Healthcare professional in England and Wales. There are approximately 130, 000 patients on Home Oxygen at any time. No specialist training is required to request Home Oxygen and there was previously no mandatory evaluation of risk before it was requested for patients. However, fatalities and serious incidents occurred, and local risk assessments were developed by several Home Oxygen teams to mitigate these risks. It was identified nationally that a risk evaluation for all new patients should be developed, resulting in the IHORM which was introduced for mandatory use from 1st August 2017. The IHORM identifies a number of risks and has clear actions for clinicians to follow if the patient's responses are too high risk to install oxygen. Method: Incident data was collated for 2 year periods before and after roll out of the IHORM. Data was categorised into 5 levels oxygen incidents. Data for level 3 (minor), 4 (injury) and 5 (fatality or other serious incidents) was retrospectively analysed. Results: 454 incidents were reported before and 327 incidents after IHORM introduction. Following the introduction of IHORM:- Level 5 serious incidents associated with smoking and fires reduced by 62%. No incidents related to use of emollients oxygen and air mattresses were reported. Number of falls relating to oxygen tubing fell by 15%. Overall IHORM evaluated risks reduced by 28%. Conclusion: The implementation of compulsory risk assessment using IHORM led to an important reduction in adverse events in home oxygen patients. Recommendations: Standardisation of all reporting including incident levels and terminology by NHS home oxygen suppliers is required. Repeat risk assessment of all current smokers with oxygen insitu as 'safe' smokers should be recommended. As health changes may result in increased risk. Education training modules available to NHS staff who complete IHORM Standardisation of ex-smoker definition Rigorous assessment of frailty risks Recognition of NICE COPD Guidelines 1 and the future BTS COPD guideline recommendations. Reference: Chronic obstructive pulmonary disease in over 16s: diagnosis and management. NICE guideline [NG115] webaccessed 11/7/19 https://www.nice.org.uk/guidance/ng115